SEARCHING FOR THE TRUE SELF: THE WAY OF NONDUAL WISDOM - T. V. Danylova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. This paper attempts at analyzing the phenomenon of the human self in the Western and Eastern traditions, its dissociation and alienation in the contemporary world, and meditation as a way to the True Self. Methodology. The author used anthropological integrative approach, philosophical hermeneutics, along with transpersonal approach. Theoretical basis and results. To overcome the feelings of loneliness, isolation, and alienation, modern individuals need to break through to the spiritual pole that provides them with ever new and deeper meanings; to go beyond the limits of dual thinking to perceive the true nature of their mind. The representatives of the Eastern religious and philosophical schools paid considerable attention to the problem of alienation, loneliness, and the ways of overcoming it. Trying to achieve the state of absolute unity, the Eastern traditions use meditation techniques, which have been developed over the centuries. Meditation contributes to the experience of the unity of existence - the state, in which the very idea of the own self disappears and the «subject – object» unity arises. Reaching the state of nonduality, meditators experience their deep involvement in all that exists. Their mind is filled with absolute peace and harmony; everything has deep meaning and value. They feel freedom. People become existentially absorbed in the world - the changeful world of artists and children, the world where everyone and everything undergo transformations. Meditation leads to the new horizons, to the awareness of infinity and diversity of life. Originality. Human integration into the cosmic body of the universe transforms their perception of the world. Returning to the world of space, time, and causation, being unable to escape the world of differentiation, individuals face a new dilemma. This entails internal conflict. To overcome it, they learn to cultivate the unbounded mind. Incorporation of mindfulness into our daily life brings many benefits. However, the molecular mechanisms of these processes are still insufficiently studied. Nowadays, scientists actively explore the effects of meditative, mind-expanding practices on the physical and mental health. Conclusions. Since the modern life becomes more tough and complex, people seek the way to a harmonious, balanced, and happy existence. It is therefore no coincidence that the spiritual heritage of the East has attracted vivid attention and considerable interest. The Eastern spiritual practices can be used as a guide to a happy human life.